Attitudes to mobile phone usage to road safety - Nur Azyan Wahidah, Md Azmi (2016)
Nowadays, mobile phones have become a common gadget which allows people to access social network sites. As technology advances further, there is a need to be aware of its impact on driver behavior. The use of mobile phones while driving is one of the contributing factors in road accidents. Due to this problem, it resulted in accidents occurring more frequently due to the negligence of the driver’s intent to focus instead on a mobile phone in front of it. This is because the response of the body against cell phone use will lead to dangerous driving. This research is more likely to determine the group of UMP community which is the most vulnerable to distracted driving due to the used of mobile phone and also to segregate high- risk and non- high risk groups in the community by using the mobile phone during driving. In addition, this research was carried out through a literature review of the topics that related to the factors that related to the distracted in driving. A questionnaire survey was used to obtain the information needed to meet the requirements of this inquiry. The questionnaire was distributed to 120 respondents of group UMP communities and all of it was responding to the survey. The distribution was involved with three (3) groups of professional which is student, academic staff and non-academic staff. From the questionnaire survey, the analysis shows that four (4) parts had been divided to identify the attitude of mobile phone usage to road safety. All data were analyzed using the software Statistical Package for Social Science 17 (SPSS) to acquire min statistic and standard deviation. From the questionnaire, it found that group that most vulnerable to distracted driving used by mobile phone during driving are male respondent. The most activities distracted during driving are talking to another passenger while driving. It shows that the majorities of the respondent are sometime used their mobile phone while driving This research shows that most of the group UMP communities are not using their mobile phone while driving and the attitude of mobile phone usage to road safety in UMP campus are not worse.